Influence of the high-power ion-beam irradiation of a hydroxyapatite target on the properties of formed calcium phosphate coatings; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 7, iss. 5 - Bleykher (Bleicher) G. A. Galina Alekseevna (2013, 2013)
Title screen